Design of a Home Door Security System Based on NodeMCU ESP32 Using a Magnetic Reed Switch Sensor and Telegram Bot Application - Ramadhani, Syahri; Putri, Dhanny Permatasari (Sinkron : jurnal dan penelitian teknik informatika, 2023)
With very rapid technological advancements, it is not possible now that all activities can be carried out quickly, easily, and instantly. The Internet of Things (IoT) allows us to solve various problems by making some devices communicate with each other across the virtual world network. This study uses the prototyping method by explaining how to design a home door security system that can be controlled by a smartphone with a WiFi connection and can use a card consisting of a chip connected to a reader. The design of this tool consists of several stages, namely designing a block diagram of how the circuit works, and designing hardware (Hardware) and software (Software). From the results of system testing, it can be seen that when conducting RFID testing by tapping the card on the reader. The system is successful and the door can be opened according to the NUID card that has been registered with the program and it can fail by using a card that is not registered in the system. Which indicates the test results are working properly. The working capability of the system on the door security device is as expected and the response from the magnetic reed switch sensor as input from the notification is very good. This system using RFID functions to make it easier for users to control the door of the house with a smartphone connected to wifi so that users don't just use conventional keys.